2000
DOI: 10.1148/radiology.215.2.r00ma42563
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Abnormal Interpretation and Cancer Detection Ratios to Assess Reading Volume and Reader Performance in a Breast Screening Program

Abstract: Standardized abnormal interpretation ratios and standardized cancer detection ratios provide a method of comparing two important performance measures in a screening program. A minimum of 2,500 interpretations per year is associated with lower abnormal interpretation rates and average or better cancer detection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 11 publications
5
58
3
1
Order By: Relevance
“…A few studies [15][16][17][18][19] have examined the association of radiologists' interpretation volume with their performance. Four of them [15][16][17][18] were conducted as experiments; since performance in a test environment appears to be unrelated to performance in actual practice, 20,21 the relevance of the results of these studies to our purposes is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies [15][16][17][18][19] have examined the association of radiologists' interpretation volume with their performance. Four of them [15][16][17][18] were conducted as experiments; since performance in a test environment appears to be unrelated to performance in actual practice, 20,21 the relevance of the results of these studies to our purposes is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Our study support findings from five studies showing volume to be of importance. [18][19][20][21][22] For example, Theberge et al 21 showed that radiologist who read more than 2,000 mammograms per year had higher sensitivity while maintaining low specificity. Our results are in contrast with those of previous studies finding that increased volume may not necessarily increase performance.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologist training in general has been associated with increased performance. [12][13][14][15][16][17] Data on the relationship between volume read per radiologist and performance are, however, conflicting, 13,[18][19][20][21][22] whereas associations have been found between some other indicators of radiologists' experience and performance. [23][24][25] However, most studies focused on mammography screening, and no large community based study has evaluated the association between organisational factors and performance of diagnostic mammography.…”
mentioning
confidence: 99%
“…Kan ve ark. [39], yılda en az 2500 MG okuyanlarda kanser saptama oranının daha yüksek olduğunu bildirmiştir. Molins ve ark.…”
Section: Tarama Mamografisi Nasıl Değerlendirilmelidir?unclassified